Public projects benefiting some and harming others: Three experimental studies - Werner Güth; Anastasios Koukoumelis; M. Vittoria Levati; Matteo Ploner (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2012)
Based on an axiomatically derived provision rule allowing community members to endogenously determine which, if any, public project should be provided, we perform experiments where (i) not all parties benefit from provision, and (ii) the projects' costs can be negative. In the tradition of legal mechanism design, the proposed provision rule is widely applicable. Additionally, it relies on intuitive fairness and profitability requirements. Our results indicate that the provision rule is conducive to efficiency, despite its multiplicity of equilibria and underbidding incentives. The only condition is that the cost of the most efficient project is positive.
Keywords: C72; C92; D63; H44; 330; Public project; Bidding behavior; Procedural fairness; Öffentliches Gut; Projektfinanzierung; Auktionstheorie; Gerechtigkeit; Nichtkooperatives Spiel; Test